2015
DOI: 10.3126/ijasbt.v3i3.12566
|View full text |Cite
|
Sign up to set email alerts
|

Flowering Behaviour and Seed Yield of French Bean as Affected by Variety

Abstract: The effect of flowering pattern and floral abscission on the yield and yield attributed characters of French bean varieties were studied in a field of Bangladesh Agricultural Research Institute, Gazipur. There nine varieties were treated- (1) BARI Jharsheem-1 (2) BARI Jharsheem-2 (3) Sylhet local-1 (4) Sylhet local-2 (5) Sylhet local-3 (6) Sylhet local-4 (7) Sylhet local-5 (8) Sylhet local-6 and (9) Sylhet local-7. Among the treatments, the highest number of flower was recorded within 5 to 8 days in BARI Jhars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…[16] reported that days required to first flowering showed little differences among the various cultivars of French bean. The result is similar to the findings of [17]. The data on days required to first flowering was found to be significant in terms of different levels of nutrients on French bean (…”
Section: Number Of Leaves Per Plantsupporting
confidence: 89%
See 1 more Smart Citation
“…[16] reported that days required to first flowering showed little differences among the various cultivars of French bean. The result is similar to the findings of [17]. The data on days required to first flowering was found to be significant in terms of different levels of nutrients on French bean (…”
Section: Number Of Leaves Per Plantsupporting
confidence: 89%
“…The number of flowers per plant of French bean was significantly influenced by the three varieties [17] observed that BARI French bean-2 produced the highest number of flowers per plant while BARI French bean-1 produced the lowest number. The number of flowers per plant showed significant differences due to the application of different levels of nutrients flowers per plant (32.02) was recorded from the treatment combination of V 2 N 2 (BARI French bean-2 and cowdung @ 5 t/ha + N 90 P 30 K 45 kg/ha) while the minimum number of flower per plant (13.33) was recorded from a combination treatment of V 3 N 1 (BARI French bean-3 and cowdung @ 5 t/ha + vermicompost @ 2 t/ha) .…”
Section: Number Of Flowers Per Plantmentioning
confidence: 95%
“…Fresh green beans are sweeter than canned. This crop is also valuable in Bangladesh mostly for exporting tender beans to the European market [11]. In recent years, the Hortex Foundation, Vegetable Export Center of BRAC and some other organizations facilitated the export of this vegetable of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the crop has a well-known export quality which has attracted the attention of the Agriculture industry and exporters [3]. This crop is also valuable in Bangladesh mostly for exporting tender beans to the European market [10]. In this context, the yield of Bush bean has become an important component of vegetable production and cash income.…”
Section: Introductionmentioning
confidence: 99%